Design of an open-end slotted dual-band antenna for On/OFF body communication - Paras Chawla , Anupama Gupta (International Journal of Advanced Science and Technology, 2020)
A compact dual-band, dual -mode antenna for body centric wireless communication is presented.Antenna is designed to operate at 2.45 GHz, Industrial scientific and medical band (ISM) for on-onbody communication and 5.5 GHz, wireless local area network (WLAN) band for on-off bodycommunication. Antenna is designed using coplanar waveguide feed and open-end slot cut monopoleradiator.Proposed structure has overall dimensions of 14 × 25 ×0.51 mm3. Wide bandwidth of 300MHz and 400 MHz is obtained for the lower and upper band respectively. High gain of 4.72/3.28 dBi,low Sar value of 0.839/1.56 W/Kg makes antenna appropriate for body centric communication.